2020
DOI: 10.1556/2006.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and clinical characteristics of Compulsive Sexual Behavior Disorder (CSBD): A cluster analysis in two independent community samples

Abstract: Background and aimsCompulsive Sexual Behavior Disorder (CSBD) is characterized by a persistent failure to control intense and recurrent sexual impulses, urges, and/or thoughts, resulting in repetitive sexual behavior that causes a marked impairment in important areas of functioning. Despite its recent inclusion in the forthcoming ICD-11, concerns regarding its assessment, diagnosis, prevalence or clinical characteristics remain. The purpose of this study was to identify participants displaying CSBD through a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 93 publications
(120 reference statements)
4
34
0
2
Order By: Relevance
“…Excessive and problematic engagement in OSAs (also known as cybersex addiction, online sexual compulsivity, or Internet sex addiction) is characterized by symptoms such as: (a) loss of control over OSA, (b) persistent desire and/or unsuccessful efforts to stop, reduce, or control OSA; (c) use of OSAs as a coping mechanism; and (d) social, physical, and psychological consequences derived from the OSA (Wéry & Billieux, 2017). Excessive and problematic engagement in OSA may be classified as a subtype of Compulsive Sexual Behavior Disorder (CSBD) (Gola et al, 2020), an impulse control disorder characterized by a persistent failure to control intense and recurrent sexual impulses, urges, and/or thoughts, resulting in repetitive sexual behavior that causes a marked impairment in important areas of functioning (Castro-Calvo et al, 2020;Kraus et al, 2018). The identification of this clinical condition is much more complex than simply attend to the time invested online for sexual purposes (Bőthe et al, 2020); its diagnosis actually requires a more in-depth assessment of the nature and context of individual's online sexual problems, as well as a comprehensive knowledge on how this condition is manifested in different populations (e.g., in terms of symptoms and other pathological indicators).…”
Section: Excessive and Problematic Engagement In Osas Across The Lifespanmentioning
confidence: 99%
“…Excessive and problematic engagement in OSAs (also known as cybersex addiction, online sexual compulsivity, or Internet sex addiction) is characterized by symptoms such as: (a) loss of control over OSA, (b) persistent desire and/or unsuccessful efforts to stop, reduce, or control OSA; (c) use of OSAs as a coping mechanism; and (d) social, physical, and psychological consequences derived from the OSA (Wéry & Billieux, 2017). Excessive and problematic engagement in OSA may be classified as a subtype of Compulsive Sexual Behavior Disorder (CSBD) (Gola et al, 2020), an impulse control disorder characterized by a persistent failure to control intense and recurrent sexual impulses, urges, and/or thoughts, resulting in repetitive sexual behavior that causes a marked impairment in important areas of functioning (Castro-Calvo et al, 2020;Kraus et al, 2018). The identification of this clinical condition is much more complex than simply attend to the time invested online for sexual purposes (Bőthe et al, 2020); its diagnosis actually requires a more in-depth assessment of the nature and context of individual's online sexual problems, as well as a comprehensive knowledge on how this condition is manifested in different populations (e.g., in terms of symptoms and other pathological indicators).…”
Section: Excessive and Problematic Engagement In Osas Across The Lifespanmentioning
confidence: 99%
“…To date, most studies have focused on the negative outcomes of CSB (see Walton et al, 2017, for a recent review) and/or on the profile of people with higher levels of CSB with respect to factors such as gender (e.g. Castro-Calvo et al, 2020), religiosity (e.g. Grubbs et al, 2020), and personality dispositions (Efrati et al, 2019; Zilberman et al, 2018).…”
mentioning
confidence: 99%
“…In a cluster analysis, Vaillancourt-Morel et al [ 27 ] reported higher numbers for the compulsive cyberpornography user cluster (11.8%), with men being more likely to belong to this cluster. In a community sample, Castro-Calvo et al [ 28 ] reported 7.8% of individuals meeting the CSBD cut-off (HBI).…”
Section: Resultsmentioning
confidence: 99%
“…Especially high frequencies were reported in student populations, with frequencies as high as 27.9% of males and 9.2% of females meeting the HBI cut-off [ 29 ]. In a study measuring CSBD with a composite index based on previously validated scales (HBI, SCS and SAST), the number decreased to 10.1% of students (of which 30.6% were female) endorsing CSBD [ 28 ]. Nevertheless, the gender effect with higher indices for males was reported in numerous student samples and with a variety of measurements (HDSI, [ 30 ]; HD and HBCS [ 31 ]; SCS [ 32 , 33 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation